The Implementation Of Podcast In Teaching Listening At The First Semester Students Of IKIP PGRI Madiun. - Rengganis Siwi Amumpuni (Jurnal Pendidikan Edutama, 2016)
The Implementation of Podcast in Teaching Listening at the First Semester Students of IKIP PGRI Madiun. This research is aimed at describing the process, the problems and solusions of the implementation of Podcast in teaching listening at the first semester students of IKIP PGRI Madiun. The type of research applied is a descriptive qualitative research. The reseach is conducted in English teaching Department of IKIP PGRI Madiun. The sample is class 1A chosen by purposive sampling technique. The collecting of the data is done by observation and interview method. To analyze the data, first reduce data, second classify the data to answer the statement of the problem, and third, interpret and conclude the data. The result of this research points out that the implementation of Podcast consists of three steps, namely, pre activity, whilst activity and post activity. Meanwhile, the problems arisen in teaching listening by using podcast are the lecturer says that the preparation has some difficulties in downloading the material from internet and the problem concerns with the crowded teaching situation. The solutions used to face the problem arisen are the lecturer should be more creative to find the material in podcast that is completely appropriate with the teaching objectives and to solve the problem of crowded teaching situation, the lecturer frequently asks the students to keep focusing on the stages of learning process while observing.Key words: Metode Demonstrasi (dengan IT), dan Hasil Belajar.